Introduction to cosmic inflation and dark energy - Dimopoulos, K. (Konstantinos) (Boca Raton : CRC Press, 2021)
"Cosmic inflation and dark energy hold the key to the origin and the eventual fate of the Universe. Despite the increasing prominence of these subjects in research and teaching over the past decade or more, no introductory textbook dedicated to these topics has been previously published. Dr Konstantinos Dimopoulos is a highly regarded expert in the field, and an experienced communicator of the subject to students. In this book he provides advanced undergraduate and early graduate students with an accessible introduction and equips them with the tools they need to understand the cosmology of cosmic inflation and dark energy. Features: Provides a concise, pedagogical "crash course" in big bang cosmology, focusing on the dynamics and the history of the Universe, with an emphasis on the role of dark energy Chapters contain questions and problems for readers to test their understanding The first book to make cosmic inflation and dark energy accessible to students"--
OCLC-licensed vendor bibliographic record.
Keywords: Cosmology -- History; Dark energy (Astronomy); Big bang theory; SCIENCE / Astrophysics & Space Science; SCIENCE / Physics; SCIENCE / Mathematical Physics